Complexos de paládio(II) derivados de calcogênios (Se e Te): síntese, caracterização e aplicação para a produção fotocatalítica de hidrogênio - Razera, Giovanny Ferro (2022)
This work describes the synthesis and characterizartion of four new palladium complexes derived from palladium selenolates: [Pd4(SeC6H4-p-F)4(OAc)4]·DMF (1), [Pd4(SeC6H4-p-Cl)4(OAc)4]·DMF·H2O (2), [Pd4(SeC6H4-p-Me)4(OAc)4]·2CHCl3 (3), [Pd4(SeC6H4-o-OMe)4(OAc)4]·4CHCl3 (4), and a novel palladium complex of a tellurinic anhydride [(1,3-OMe)2C6H3Te)2OPd(O2C7H4Cl)2] (5). In the first step of this work the reactions between (SeAr)2 and Pd(OAc)2 were investigated, that led to the formation of isostructural tetranuclear species, assuming a paddle-wheel type geometry in the solid state, with a core based on [Pd4Se4]. In the second step, it was planned the synthesis of species M–Te–O, by means of the reactions between (TeAr)2, Pd(OAc)2 and meta-chloroperoxybenzoic acid, which led to the formation of 5, a mononuclear species in the solid state, containing a core based on [Pd(Te2O)]. Four of these complexes derive from selenium, and one from tellurium. The five compounds obtained were characterized by single-crystal X-ray diffraction, infrared spectroscopy, UV-Vis spectroscopy in solution, as well on the solid-state on diffuse reflectance mode, elemental analysis and high resolution mass spectrometry. All five complexes synthesized during the work were applied as sentitizers of mesoporous TiO2 for heterogeneous photocatalytic hydrogen evolution from water splitting reaction. Among the complexes applied as m-TiO2 sensitizers, complex 4 was the most promising, with a production of approximately 12 mmol of H2(g) per gram of photocatalyst.